Larvicidal efficacy screening of Anacardaciae crude extracts on the dengue hemorrhagic vector, Aedes aegypti - Zuharah, W.F.; Fadzly, N.; Zakaria, R.; Juperi, S.; Asyraf, M.; Dieng, Hamady (Malaysian Society of Parasitology and Tropical Medicine, 2014)
Vector-borne diseases are still rife because of the re-emergence of diseases transmitted by mosquitoes. The objective of this paper is to evaluate the larvicidal efficacy of crude leaf extract of Mangifera indica, Gluta renghas, and Melanochyla fasciculiflora against vector of dengue hemorrhagic fever, Aedes aegypti. These plant species are endemic species and widely distributed in Malaysian forests. Leaves of Ma. indica, G. renghas and M. fascculiflora were collected from Teluk Bahang National Park, Penang Malaysia. Fractions of leaves were segregated, air-dried, powdered and extracted using Soxhlet with methanol. The solvent was removed by using rotary evaporator to obtain the crude extract. Using WHO standard larval bioassay test method, third instar larvae of Aedes aegypti were exposed to concentration ranging from 200- 4500 ppm of methanol extract for all plant species. Larval mortality was observed after 24 hours exposure. The highest susceptibility and toxicity was recorded by Mangifera indica with the lowest concentration at 800 ppm followed by M. fasciculiflora and G. renghas. This indicates that crude plant extract is very effective in killing Ae. aegypti mosquitoes. This finding may lead to new low cost alternative, environmentally friendly method for mosquito control programs. To our knowledge, this is the first report on larvicidal bioefficacy from endemic Malaysian plants.